Fräulein Elses Begehren: Kolorierungen von Emotionen in Arthur Schnitzlers Novelle und in Manuele Fiors Comic - Tacke, Alexandra (Studia Germanica Posnaniensia, 2015)
The following article compares the representation of nakedness in the novella Fräulein Else (1924) by Arthur Schnitzler and in the Graphic Novel Fräulein Else (2009) by Manuele Fior. While Schnitzler is inserting parts of the musical score Carnaval by Robert Schumann at that point of the text, when Fräu-lein Else is showing herself naked publically, and thus refuses to give more details, Fior cites in his Comic adaption the famous painting Nuda Veritas by Gustav Klimt, which was scandalized at its time. Slight changes are made also at the ending: while Schnitzler refers to the Orpheus-Eurydike-Myth, Fior compares the interior monologue of Fräulein Else to the myth of Echo.